Knowledge of occupational health problems and practice of safety measures among traffic police of Kathmandu metropolitan. - Sapkota, Radhika (2014)
ABSTRACT: Occupational health is the promotion maintenance of the highest degree of physical, mental and social well- being of workers in all occupation by preventing departures from health controlling risks and the adaptation of work to people, and the people to their jobs (ILO/WHO 1950). WHO estimated that at a global level occupational noise exposure was the cause of the hearing impairment in 16% of those people with a moderate or greater hearing loss. Study aims to find out the knowledge of OHP and practice safety measures among traffic police of Kathmandu metropolitan city. A cross-sectional analytical study was undertaken so as to conduct this research. Pretesting of instrument was done in Kalanki to modify the questions to maintain the validity and reliability of research instrument. Data was collected by using an open-ended and closed -ended question. The collected raw data was managed with necessary coding and analyzed with the backup of SPSS software. The study duration was of 6 months for the completion of whole activities. Median age of traffic police was 24. Majority of the respondents (81.3%) represented the age group 20-30 years. 68.7% traffic police works more than 10 hours per day. 98.7% had heard about OHP. The entire respondent had heard about the PPM. Till six month 68% of traffic police experience health problem. 63.3% informed the concern authority on their health problems. 68% had received medical checkup. Although they have knowledge of occupational health problems and PPM is being used health problems in traffic police is not reduced because of lack of good quality PPM, workload, and polluted environment and so on. Government has done very little effort to project the occupational health of traffic police. They are not even provided enough protective materials for their job. Traffic police have to duty more than 10 hours a day but facilities provided to them are very low.